Ethical Considerations in the Collection and Handling of Financial Data in ETC - Pankaj Lembhe, Pankaj Lembhe (International Journal of Computing and Engineering, 2024)
Purpose: This research note provides some practical advice on accessing financial reports on the internet and the collection of associated data for subsequent analysis. Methodology: Potential methodological problems, such as biases or conflicts of interest, should be acknowledged and strategies for addressing them should be outlined. Findings: Additionally, the confidentiality and privacy of individuals or companies whose financial data is being collected must be protected. Unique contribution to theory, practice, and policy: The guidance on accessing and collecting financial data online contributes to both the theoretical framework of financial analysis and practical applications for researchers and practitioners, ensuring ethical standards are maintained.